Perbedaan perilaku mencuci tangan sebelum dan sesudah diberikan pendidikan kesehatan pada anak usia 4-5 tahun - Apriany, Dyna (Jurusan Keperawatan FIKES UNSOED, 2012)
Hand washing is one of the sanitation actions by washing hand and fingers using flowing water and soap by people to clean and break the germ chain. It is caused by diare. The aim of the research is to know the difference washing hand habit before and after being given health education to children. The method of research is one group pretest posttest design. The pretest is given before conducting the intervention. After getting the intervention, the posttest is conducted. The research conducted on July 2011 in At-Taqwa Cibeber Cimahi with 32 samples by using sampling purposive technique. The t-test result shows that there is difference hand washing habit before and after being given education with p value = 0,0001. It is recommended for education institution to foster the high health value principal such as hand washing before and after eating or after doing activities. Furthermore the principal of health or healthy behavior should be their habit from early age.